PREVALENSI ANAK CEREBRAL PALSY DI INSTALASI REHABILITASI MEDIK RSUP PROF.DR.R.D.KANDOU MANADO PERIODE 2015 - Sitorus, Fransisca Sitorusca Santa Anna Boru; Mogi, Theresia Isye; Gessal, Joudy (FAKULTAS KEDOKTERAN UNSRAT, 2016)
Introduction: Cerebral Palsy (CP) is a nonprogressive syndromes of posture and motor impairment, causing activity limitation, and often accompanied cognitive impairment or visual deficits. The etiology of CP is Pranatal, Natal and Postnatal. Nearly half of these disabilities are diagnosed in preterm born children and the other one in postterm born children. CP is usually classified based on Topography (Monoplegic, Hemiplegic, Diplegic, Triplegic, Quadriplegic) and Motoric function which often result from various areas damage during development of the nervous system or in the first 2 years of life. The parents realize their child suffering CP at the age of 3-5 years old. Methods: a descriptive study with retrospective method by collecting medical records patient with CP. Result: In 33 case of CP, more common in the age 1-5 years old as 19 cases, the most frequent gender is male as 18 cases, the most frequent topography is Quadriplegic as 26 cases and by motoric function is spastic as 33 cases (100%). Conclussion: The Prevalence of Children with Cerebral Palsy in Medical Rehabilitation Installation of RSUP.PROF.DR.R.D. Kandou Manado in 1 january 2015 â€“ 31 Desember 2015 based motoric function is Spastic. Keyword: Cerebral Palsy (CP) Â Pendahuluan: Cerebral Palsy (CP) adalah sindroma postur dan gangguan motorik yang nonprogresif yang menyebabkan terbatasnya aktivitas dan seringkali disertai gangguan kognitif atau defisit visual. Etiologi CP dibagi menjadi Pranatal, Natal, dan Postnatal. Hampir setengah dari disabilitas ini didiagnosis pada anak yang lahir kurang bulan. CP biasanya diklasifikasikan berdasarkan Topografi (Monoplegi, Hemiplegi, diplegi, Triplegi, Quadriplegi) dan Klasifikasi fungsi gerak motorik yang berasal dari kerusakan berbagai area selama perkembangan sistem saraf atau dalam dua tahun kehidupan pertama. Orang tua menyadari anak menderita CP pada usia 3-5 tahun. Metode: Penelitian deskriptif dengan pendekatan retrospektif, dengan cara mengumpulkan rekam medik pasien CP. Hasil: Pada 33 kasus CP, didapatkan usia terbanyak 1-5 tahun sebanyak 19 kasus, Jenis kelamin terbanyak laki-laki yaitu 18 kasus, Topografi terbanyak yaitu Quadriplegi sebanyak 26 kasus dan fungsi gerak motorik terbanyak adalah Spastik yaitu 33 kasus (100%). Kesimpulan: Prevalensi anak Cerebral Palsy di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2015 â€“ 31 Desember 2015 berdasarkan fungsi gerak motorik terbanyak adalah Spastik. Kata Kunci: Cerebral Palsy (CP)